The Influence Of Personal Branding On Instagram Followers' Loyalty: A Case Study Of Fadil Jaidi - Khaerunnisa Az Zahra; Izzati Rizal (Journal of Communication, Sustainability, and Empowerment, 2025)
This quantitative study investigates the influence of personal branding on Instagram follower loyalty, specifically examining Fadil Jaidi's account (@fadiljaidi) with 13.7 million followers. Using purposive sampling, 278 respondents who met specific criteria (minimum 17 years old, following the account for at least 6 months, and actively engaging with content) participated in this research. Personal branding was measured through four dimensions: authenticity, visibility, distinctiveness, and consistency, while follower loyalty was assessed through behavioral loyalty, attitudinal loyalty, and advocacy loyalty. Data collection utilized online questionnaires with a 4-point Likert scale, analyzed using simple linear regression via SPSS. Results demonstrate a strong positive correlation (r = 0.654) between personal branding and follower loyalty, with the regression equation Y = 12.02 + 0.54X indicating that each unit increase in personal branding results in a 0.538 unit increase in follower loyalty. The coefficient of determination (R² = 0.427) reveals that personal branding explains 42.7% of follower loyalty variance. Consistency emerged as the strongest personal branding dimension (971.25 index value), while attitudinal loyalty scored highest among loyalty dimensions (973.5 index value). These findings provide empirical evidence that authentic, consistent, and distinctive personal branding strategies significantly enhance follower commitment, particularly through family-centered content that creates unique positioning in competitive social media landscapes.